Relação de índices fenológicos e resistência a penetração do solo com a produtividade de algodão em pluma - TÚLIO RUSSINO CASTRO (2024)
Cotton is a crop of great economic importance in Brazil and around the world, which is why a lot of research and technologies are applied to ensure its maximum development. This study sought to evaluate how trail analysis and geostatistics can be applied in commercial cotton areas to understand and identify characteristics that contribute directly or indirectly to cotton lint productivity. Chapter 1 seeks to relate cotton lint productivity and phenological indices of cotton plants, through the correlation network and trail analysis. Chapter 2 aims to evaluate the phenological indices of cotton in cultivation areas through the analysis of spatial variability. Chapter 3 aims to analyze the spatial variability of soil’s resistance penetration in a cotton area. The results obtained indicate that trail analysis can highlight the correlation between cotton lint productivity and phenological indices of cotton plants, with the phenological indices number of bolls and total fresh mass of the cotton plant being the main phenological indices that positively influence productivity. of cotton. Furthermore, mapping cotton-producing areas allows for evaluating the correlation between productivity and plant variables, where cotton productivity is directly positively related to the number of bolls and negatively to the insertion height of the first boll in cotton plants. Although there is an inversely proportional correlation between cotton lint productivity and soil penetration resistance, the lower the penetration resistance, the greater the cotton productivity. Therefore, geostatistics should be used to identify cotton characteristics, being applied as a tool to increase the productivity of cultivation areas.